Estimation de l’allergie pollinique dans la ville de Annaba (Algérie) - NECIB, A; BOUGHEDIR, L; AIDAOUISARI, G. (My University, 2020)
The aim of this work is to realize a clinical investigation, during two years, to improve the knowledge on the prevalence of allergies in general and, pollinosis in particular, in the region of Annaba (Northeast of Algeria). The clinical results of the analysis of the pollen allergen frequency of the 230 patients, show that Cypress pollen sensitization occupies the first position (29,26%), followed by the pollen of Olivier and Cereals with an equal percentage (24.39%). Pestnut pollen has 19.51% and grass pollen with 17.07%. © 2021 Revue Algérienne d’allergologie et d’immunologie médicale. All rights reserved.